2018
DOI: 10.1101/492165
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Homeostatic and tumourigenic activity of SOX2+ pituitary stem cells is controlled by the LATS/YAP/TAZ cascade

Abstract: 29 30 SOX2 positive pituitary stem cells (PSCs) are specified embryonically and persist throughout 31 life, giving rise to all pituitary endocrine lineages. We have previously shown the activation 32 of the MST/LATS/YAP/TAZ signalling cascade in the developing and postnatal mammalian 33 pituitary. Here, we investigate the function of this pathway during pituitary development and 34 in the regulation of the SOX2 cell compartment. Through loss-and gain-of-function genetic 35 approaches, we reveal that restrictin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…Analysis of global gene expression signatures using 'Gene Set Enrichment Analysis' (GSEA)(Subramanian et al, 2005) identified a significant enrichment of molecular signatures related to EMT, adherens and tight junctions in the EGFP + fraction, characteristic of the SOX2 + population(Figure 3figure supplement 1B). The SOX2 + fraction also displayed enrichment for genes associated with several signalling pathways known to be active in these cells, including EGFR (Iwai-Liao et al, 2000), Hippo(Lodge et al, 2016;Lodge et al, 2019;Xekouki et al, 2019), MAPK(Haston et al, 2017), FGF(Higuchi et al, 2017), Ephrin(Yoshida et al, 2015;Yoshida et al, 2017) and p53 (Gonzalez-Meljem et al, 2017) (Figure 3figure supplement 1C, Supplementary File 1). Additionally, PI3K, TGF and BMP pathway genes were significantly enriched in the SOX2 + population(Figure 3figure supplement 1C, Supplementary File 1).…”
mentioning
confidence: 97%
“…Analysis of global gene expression signatures using 'Gene Set Enrichment Analysis' (GSEA)(Subramanian et al, 2005) identified a significant enrichment of molecular signatures related to EMT, adherens and tight junctions in the EGFP + fraction, characteristic of the SOX2 + population(Figure 3figure supplement 1B). The SOX2 + fraction also displayed enrichment for genes associated with several signalling pathways known to be active in these cells, including EGFR (Iwai-Liao et al, 2000), Hippo(Lodge et al, 2016;Lodge et al, 2019;Xekouki et al, 2019), MAPK(Haston et al, 2017), FGF(Higuchi et al, 2017), Ephrin(Yoshida et al, 2015;Yoshida et al, 2017) and p53 (Gonzalez-Meljem et al, 2017) (Figure 3figure supplement 1C, Supplementary File 1). Additionally, PI3K, TGF and BMP pathway genes were significantly enriched in the SOX2 + population(Figure 3figure supplement 1C, Supplementary File 1).…”
mentioning
confidence: 97%
“…FAT4/DCHS1 may be involved in cell movements during development, which is consistent with their known role in planar cell polarity (10,11,25), often an important pathway during dynamic rearrangement and migration of cells. In the anterior pituitary they are unlikely to act upstream of YAP for this purpose, as previous work deregulating YAP levels during development did not result in medio-lateral morphogenesis defects (36).…”
Section: Discussionmentioning
confidence: 85%
“…The VECTOR Laboratories ImmPRESS kit was used for antibodies against SF1 according to the manufacturer's instructions. The PerkinElmer TSA kit was used for antibodies against DCHS2 and FAT2, as previously described (36). After primary antibody incubation, slides were washed in PBST, then incubated with appropriate secondary antibodies (biotinylated goat anti-rabbit, 1:300, Abcam ab6720; biotinylated goat anti-mouse, 1:300 Abcam ab6788) and incubated with fluorophore-conjugated streptavidin (1:500, Life Technologies, Thermo Fisher Scientific, S11223) for 1 hour at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining large group of 6 clusters expressed SOX2 , SOX9 , and the Hippo pathway effectors WWTR1 (a.k.a. TAZ ) and YAP1 ( 17 and reviewed in 18 ; Fig. 3d and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%